hello,

I'm trying to recall how to do this and I got stuck big time... I would be most grateful for any help

problem is :

I'll fix it in latex as soon it work with limits

\lim_{n \to \infty} ( \frac {1}{n^2} + \frac{2}{n^2} + \frac{3}{n^2} + ... + \frac{n-1}{n^2} )

and I recall that "limit of sum" is equal to "sum of limits"... something like ::

if is \lim_{n \to \infty} f(x) = A and \lim_{n \to \infty} f(x) = B than

\lim_{n\to \infty} ( f(x) +- g(x) ) = lim_{n\to \infty} f(x) +- lim_{n\to \infty} g(x)

and if I apply that to problem that I have, result would be zero but book says something else so now I'm in big trouble....

I also have more or less the same another problem but it's to "ugly" to write it without LATEX so...

what do I do wrong ?